Recent Advances and Updates in Trigeminal Autonomic Cephalalgias - Wei, Diana Y.; Goadsby, Peter J. (Seminars in Neurology, 2022)
Trigeminal autonomic cephalalgias (TACs) are discrete primary headache disorders, characterized by severe unilateral head pain, typically trigeminal distribution, with ipsilateral cranial autonomic symptoms. The conditions within this group are hemicrania continua, cluster headache, paroxysmal hemicrania, and short-lasting unilateral neuralgiform headache with conjunctival injection and tearing and short-lasting unilateral neuralgiform headache with autonomic symptoms. Several advances have been made in understanding the pathogenesis and evolving treatment options in TACs. This review will outline the advances and updates in each TAC.
Keywords: trigeminal autonomic cephalalgia; cluster headache; paroxysmal hemicrania; hemicrania continua; SUNCT/SUNA/SUNHA